1982
DOI: 10.1152/ajpendo.1982.242.6.e451
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis in chronic streptozotocin-induced diabetes mellitus in the rat

Abstract: Calcium homeostasis was studied in freely fed control, streptozotocin diabetic, long-term and short-term insulin-treated diabetic rats 7 wk after the induction of diabetes. In contrast to the short-term (5-12 day) diabetic rat model, intestinal absorption of calcium was markedly enhanced in chronically insulin-deficient animals. Moreover, conventional balance studies showed that these animals were in positive calcium balance despite severe hypercalciuria. Intestinal hyperabsorption of calcium in long-standing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 33 publications
5
28
2
Order By: Relevance
“…Employing short-term (2-week) animal models of streptozotocin diabetes, the low BMD observed in insulinopenic diabetes was earlier explained by secondary hyperparathyroidism and increased bone resorption resulting from a negative calcium balance (impaired intestinal calcium absorption; hypercalciuria) (69,70). Using more appropriate animal models of chronic diabetes (8-10 weeks), and employing time-spaced tetracycline labelled bone histomorphometry, bone formation and resorption were found to be markedly suppressed (71,72,73,74).…”
Section: Bone Turnovermentioning
confidence: 99%
“…Employing short-term (2-week) animal models of streptozotocin diabetes, the low BMD observed in insulinopenic diabetes was earlier explained by secondary hyperparathyroidism and increased bone resorption resulting from a negative calcium balance (impaired intestinal calcium absorption; hypercalciuria) (69,70). Using more appropriate animal models of chronic diabetes (8-10 weeks), and employing time-spaced tetracycline labelled bone histomorphometry, bone formation and resorption were found to be markedly suppressed (71,72,73,74).…”
Section: Bone Turnovermentioning
confidence: 99%
“…disease on bone (1,2, 7,14,15,21,26,31,33,39,45) as well as the mechanisms by which it affects skeletal tissue and calcium homeostasis (10,19,22,29,36,38). Levin et al (21) suggested that the skeletal effects of diabetes are part of the underlying systemic condition, since they occur early and are unrelated to either the presence or absence of insulin dependence, or to disease duration.…”
mentioning
confidence: 99%
“…A dysfunction of the calcium metabolism has been reported to occur in untreated insulin-dependent diabetes mellitus [3]. The basal levels of cytosolic calcium - [Ca 2+ ] i -of renal proximal tubular cells (PTCs) of rats with streptozotocin-induced diabetes are elevated [4].…”
Section: Introductionmentioning
confidence: 99%